Highly compressible nanocellulose aerogels with a cellular structure for high-performance adsorption of Cu(II). (March 2022) - Mo, Liuting; Tan, Yi; Shen, Yulin; Zhang, Shifeng
Abstract: Cellulose-based aerogels have considerable potential for various application due to renewable, low cost, and high availability. However, mechanical robustness and functionalization remain major challenges. Here, we synthesized a compressible, recoverable cellulose nanofiber (CNF)/carboxymethyl cellulose (CMC)/branched polyethyleneimine (BPEI) aerogel via electrostatic-modulated interfacial covalent crosslinking and freeze-drying process. The porous BPEI@CNF/CMC aerogel possessed excellent mechanical compression and high-density metal-chelating groups, which exhibited fast adsorption kinetics and high adsorption capacity (452.49 mg g −1 ) in static copper adsorption process. Furthermore, BPEI@CNF/CMC aerogels displayed excellent recyclability and could still reach 85% after 10 cycles. The integrated analyses of ATR-FTIR and XPS suggested that the predominant adsorption mechanism included electrostatic interaction, ion-exchange and chelation. This strategy provides a sustainable route to fabricate efficient biomass-based adsorbents for selective copper removal from water. Graphical abstract: Image 1 Highlights: A highly compressible cellular nanocellulose aerogel was developed. Functional groups were distributed on the aerogels via crosslinking modification. The cellulose-based aerogel exhibited high adsorption capacity for Cu 2+ . There were remained high than 85% adsorption efficiency after 10 adsorption-regeneration cycles.